High Energy Density and Temperature Stability in PVDF/PMMA via In Situ Polymerization Blending - Liu, Yongbin; Liu, Zhengwei; Gao, Jinghui; Wu, Ming; Lou, Xiaojie; Hu, Yanhua; Li, Yong; Zhong, Lisheng (Frontiers in Chemistry, 2022)
Dielectrics with improved energy density have long-standing demand for miniature and lightweight energy storage capacitors for electrical and electronic systems. Recently, polyvinylidene fluoride (PVDF)-based ferroelectric polymers have shown attractive energy storage performance, such as high dielectric permittivity and high breakdown strength, and are regarded as one of the most promising candidates. However, the non-negligible energy loss and inferior temperature stability of PVDF-based polymers deteriorated the energy storage performance or even the thermal runaway, which could be ascribed to vulnerable amorphous regions at elevated temperatures. Herein, a new strategy was proposed to achieve high energy density and high temperature stability simultaneously of PVDF/PMMA blends by in situ polymerization. The rigidity of the amorphous region was ideally strengthened by in situ polymerization of methyl methacrylate (MMA) monomers in a PVDF matrix to obtain PVDF/PMMA blends. The atomic force microscopic study of the microstructure of etched films showed the ultra-homogenous distribution of PMMA with high glass transition temperature in the PVDF matrix. Consequently, the temperature variation was remarkably decreased, while the high polarization response was maintained. Accordingly, the high energy density of ∼8 J/cm3 with ∼80% efficiency was achieved between 30 and 90 °C in PVDF/PMMA films with 39–62% PMMA content, outperforming most of the dielectric polymers. Our work could provide a general solution to substantially optimize the temperature stability of dielectric polymers for energy storage applications and other associated functions.